Pemeliharaan ramah lingkungan Hotel Mandalawangi Tasikmalaya berbasis ASEAN green hotel standard - Nurlaila Fadjarwati; Nonon Rofi Nurzakiah (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2021)
Climate change is a challenge for business operations like hotel business. To deal with climate change, businesses are looking for solutions that can give a sustainability with the green hotel concept. Green hotels have environmentally friendly operations and maintenance. One of the hotels that applies the green hotel concept is the Mandalawangi Hotel located in the Tasikmalaya City. The purposes of this study was to determine the maintenance at the Mandalawangi Hotel with the technique of data collection methods by interview and observation, then comparing with the ASEAN green hotel standard criteria for certification. The results showed that the Mandalawangi Hotel has implemented 59.25% of the total criteria for ASEAN green hotel requirements. Mandalawangi Hotel requires to reduce the use of chemicals, optimize the existing operations and maintenance also carry out training programs for hotel’s human resources.